Media dictatorship how schools and educators can defend freedom of speech - Ngalande, Cedrick (Rowman & Littlefield, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2022)
"Media Dictatorship: How Schools and Educators Can Defend Freedom of Speech examines how the increasing power of the media is dangerous to democracy and modern civilization. Educators and administrators have a responsibility to develop a generation of students who value freedom of speech and can defend and sustain both democracy and civilization"--Provided by publisher.